Accessibility and readability of online patient education on cutaneous lymphomasCapsule Summary - Celine M. Schreidah, BS; Lauren M. Fahmy, BS; Brigit A. Lapolla, BS; Emily R. Gordon, BA; Bradley D. Kwinta, MD; Larisa J. Geskin, MD (JAAD International, 2023)
Background: Patients facing a cutaneous lymphoma diagnosis frequently turn to the internet for information but finding patient-accessible education may be a challenge. Objective: To investigate accessibility and readability of patient-oriented online education on cutaneous lymphomas, including cutaneous T-cell and B-cell lymphoma subtypes. Methods: This study queried a search engine for 11 cutaneous lymphoma terms, resulting in 1083 webpages. Webpages were screened using defined inclusion/exclusion criteria; literature directed to physicians and scientists was excluded. Webpages were stratified by academic/nonacademic and dermatology/nondermatology hosts and assessed by order of appearance. Readability, including text complexity, was analyzed for grade level understanding using 5 established calculators. Overall readability was assessed by Flesch–Kincaid Reading Ease. Results: Academic webpages had earlier order of appearance. There was a dearth in dermatology-hosted webpages. Rarer cutaneous lymphomas yielded fewer patient-accessible results. Search term readability significantly exceeded the American Medical Association–recommended sixth grade level (P < .001∗), with higher grade levels for cutaneous T-cell lymphoma subtype webpages than cutaneous B-cell lymphoma subtypes. Limitations: Webpage quality, accuracy, and language were not assessed. Conclusion: Current online education for cutaneous lymphomas exceeds the American Medical Association’s maximum readability recommendation. There is a need for more patient-accessible education amidst predominance of scientific literature, greater dermatology host websites, and enhanced readability of existing online education.